Content of Crude Protein, Fixed Oil and Lecithin in Sudanese Seed Accessions of Fenugreek (Trigonella foenum-graecum L.) - Bashir, Nour Ahmed Osman; Elhussein, Salah Ahmed-Ali; Taha, Ahmed Abdurrahman (Pakistan Journal of Nutrition, 2015)
We have recently reported on the variability of α and β-sapogenins in several Sudanese accessions of fenugreek seeds. Results were discussed in terms of the importance of these chemical constituents as potential raw materials for steroid drug production and their reported biological activities. This report deals with variability in protein and seed fixed oil content (particularly its lecithin fraction) in 12 selected Sudanese fenugreek seed accessions. The protein content was high, compared to other pulses and varied between 35.2 and 42.2%, on an oven-dry basis. However, the oil content was low, below 10%, in accord with published reports. The oil fatty acid composition of one accession (A1) was dominated by 18:1, 18:2, 18:0 and 16:0. Linolenic acid (18:3) was present at low relative level (below 1.0%), in contrast to some other reports. The lecithin fraction, prepared from the seed oil, amounted to a high value of 3.5% of the seed oil weight of accession A1 and contained the phospholipids phosphatidic acid, phosphatidylcholine, phosphatidylinositol, phosphatidylethanolamine, in addition to appreciable amounts of phosphatidylglycerol. The major fatty acids of the crude lecithin fraction were 18:2, 18:1 and 16:0, in addition to palmitoleic acid (16:1). The latter is likely associated with plastidic phosphatidylglycerol.